Do industries' average firm size, productivity and skill-intensity explain the border effect? - Asier Minondo (Aussenwirtschaft, 2010)
The border effect literature concludes that border-related trade costs, along with the elasticity of substitution, explain why countries trade more with themselves than with other partners.On its hand, the exporting firm literature shows that larger,more productive and more skilled-labour intensive firms are more able to bear with some of those border-related trade costs. In this paper we combine those findings and test whether a larger average firmsize, apparent labour productivity and skill content can reduce the border effect.Using a sample of European countries and an empirical model based on the gravity equation we find that a larger average size, labour-productivity and skill-content reduce the border effect significantly.
Keywords: F14; F15; 330